A man called destruction : the life and music of Alex Chilton, from Box Tops to Big Star to backdoor man - George-Warren, Holly (Viking, 2014)
Alex Chilton's story is rags to riches in reverse, beginning with teenage rock stardom and heading downward. Following stints leading 60s sensation the Box Tops ("The Letter") and pioneering 70s popsters Big Star, Chilton became a dishwasher. Yet he rose again in the 80s as a solo artist, producer, and trendsetter, coinventing the indie-rock genre. By the 90s, acolytes from R.E.M. to Jeff Buckley embodied Chilton's legacy, ushering him back to the spotlight before his untimely death in 2010. In this career-spanning and revelatory biography, longtime Chilton acquaintance Holly George-Warren has interviewed more than 100 bandmates, friends, and family members to flesh out a man who presided over--and influenced--four decades of American musical history, rendered here with new perspective through the adventures of a true iconoclast.--From publisher description.